Allelopathic Potential Of Wheat, Rye, And Radish On Crop And Weed Seed Germination - Ryan, Luke P. (My University, 2018)
Herbicide-resistant weeds have become a growing concern, increasing the need for alternative weed control methods. Natural chemical defense mechanisms in plants can inhibit the germination and growth of other surrounding plants to reduce competition, known as allelopathy. The objective of this study was to consider the allelopathic potential of hard red winter wheat, rye, and tillage radish varieties on grain sorghum, giant foxtail, and Palmer amaranth seeds. Crop treatments were eight wheat, three rye, and one radish planted and grown for eight weeks in a greenhouse. After harvesting and drying the plant biomass, 2.5% extracts were produced by soaking 2.5 g plant biomass in 100 ml water. Extracts were placed in Petri dishes with the seeds as well as a water-only control. Petri dishes were sealed, placed in a growth chamber and seed germination recorded every 48 hours. Three runs were completed with four replications of each treatment in each run. Sorghum germination was largely unaffected by the crop treatments, while the weed seeds responded to the crop treatments. Aroostook rye, Grainfield wheat, and Zenda wheat treatments resulted in significantly less germination of giant foxtail than the control in all three runs, while Everest and Duster wheats reduced germination in two of three runs. Grainfield wheat also resulted in significantly less germination of Palmer amaranth than the control in all three runs, while Zenda wheat and Aroostook rye did so in two out of three runs. These results suggest that dry plant residues of Grainfield and Zenda wheat varieties and Aroostook rye could inhibit the germination of both Palmer amaranth and giant foxtail seeds. The next step would be to evaluate their potential to reduce weed seed germination and seedling emergence when these crops are planted in the field as an alternative weed control method.